2006
DOI: 10.1309/wp59ym73l6cegx2f
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Inpatient Laboratory Testing in a Teaching Hospital

Abstract: After an inpatient phlebotomy-laboratory test request audit for 2 general inpatient wards identified 5 tests commonly ordered on a recurring basis, a multidisciplinary committee developed a proposal to minimize unnecessary phlebotomies and laboratory tests by reconfiguring the electronic order function to limit phlebotomy-laboratory test requests to occur singly or to recur within one 24-hour window. The proposal was implemented in June 2003. Comparison of fiscal year volume data from before (2002-2003) and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 22 publications
3
52
0
1
Order By: Relevance
“…Although a detailed appraisal is beyond the scope of this paper, it is worth noting that the implementation of demand management initiatives has often proved challenging and yielded variable success. 16,17 In summary, we found a wide variability in test request rates between practices that appear unrelated to disease prevalence or crude clinical outcome indicators. This suggests that despite the availability of good-quality clinical guidelines, there is still wide variation in testing practice that appears unrelated to clinical need or outcomes and may reflect instead differences in behaviour by individual clinicians when managing similar clinical problems…”
Section: -11mentioning
confidence: 77%
“…Although a detailed appraisal is beyond the scope of this paper, it is worth noting that the implementation of demand management initiatives has often proved challenging and yielded variable success. 16,17 In summary, we found a wide variability in test request rates between practices that appear unrelated to disease prevalence or crude clinical outcome indicators. This suggests that despite the availability of good-quality clinical guidelines, there is still wide variation in testing practice that appears unrelated to clinical need or outcomes and may reflect instead differences in behaviour by individual clinicians when managing similar clinical problems…”
Section: -11mentioning
confidence: 77%
“…There are growing calls for physicians to factor the financial consequences into their medical decisions. [28][29][30] Charge data offers additional information for physicians to make the most educated decisions for a patient's care.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] As such, inappropriate tests are most common in teaching hospitals. [12] Junior doctors account for a significant proportion of inappropriate pathology test ordering. [12] This is reinforced at Australian hospitals by a culture where the risk of over-ordering tests is perceived to have less serious consequences than not having ordered a required test.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Junior doctors account for a significant proportion of inappropriate pathology test ordering. [12] This is reinforced at Australian hospitals by a culture where the risk of over-ordering tests is perceived to have less serious consequences than not having ordered a required test. [9] It has been identified that within the hospital that in some situations junior nurses are pre-empting the treating doctor's pathology testing, leading to a significant proportion of unnecessary ordering.…”
Section: Introductionmentioning
confidence: 99%